Enhancing Vocabulary Retention Through Digital Storytelling on EFL Middle School Learners: A Quasi-Experimental Study in Indonesia - Roudhotul Jannah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2026)
This research investigates the effectiveness of digital storytelling as a supplementary tool for lexical fact retrieval and sustainable retention of EFL vocabulary among middle school learners. The research was conducted in particular Islamic School in Gresik, Indonesia. The selected participants were 38 eight-grade EFL learners, divided into experimental and control groups. Vocabulary knowledge was assessed through pre-test, immediate post-test, and delayed post-test conducted after two weeks. The independent sample t-test showed a significantly greater mean improvement in the digital storytelling (DST) group compared to the control group (MD = 8.04, p < .001). The vocabulary retention proved by the result of paired sample t-test which show consistency on the students’ delayed test result (p > .005). This study contributes to the growing literature on digital storytelling and its impact on lexical support. The method proved that DST is effective to enhance students’ vocabulary retention through related multimedia. Digital Storytelling enhance students’ focus and motivation to participate in class.